STRATEGIC MARKETING PRACTICES AND PERFORMANCE OF PHARMACEUTICAL COMPANIES IN SOUTHWEST NIGERIA - Ajayi Olalekan Ezekiel (MATTER: International Journal of Science and Technology, 2025)
The reports have shown that pharmaceutical industry operates in a highly competitive and dynamic environment, where strategic marketing practices are crucial for achieving sustainable performance. Despite the increasing relevance, many pharmaceutical companies in Nigeria struggle to adopt and effectively implement strategic marketing practices that align with the ever-changing market conditions. This gap in practice raises concerns about their ability to improve profitability, sales growth, customer satisfaction and market share. Consequently, the study explored strategic marketing practices and performance of pharmaceutical companies in southwest Nigeria. Four research questions were raised, and four hypotheses were formulated in line with the study's objectives. The literature was premised on four (4) theories; Schumpeter theory of innovation, dynamic capabilities theory, stakeholder theory and resource-based theory. Employing a mixed methods research design (MMR) with a survey method and convenience sampling technique, data were collected from 329 individual while in-depth interview were conducted among management teams each from the selected 9 pharmaceutical firms across the three states. Utilizing Pearson correlation and multiple regression analysis to test the hypotheses, strategic marketing practices components (collaboration strategy, product distribution strategy, marketing leadership and innovative leadership) were found to have a significant impact on performance of pharmaceutical companies (profitability, sales growth, customer satisfaction and market share). This was shown in their coefficient of determinations and significant values for the four (4) hypotheses: collaboration strategy and profitability R= 0.832; P=0.000; product distribution strategy and sales growth R= 0.864; P=0.000; marketing leadership and customer satisfaction R= 0.791; P=0.000; innovative leadership and R= 0.804; P=0.000. Therefore, the study concluded that when effective collaboration strategies were put in place by the management of the pharmaceutical firms, there is possibility of increasing the sales revenue is of the firm provision of value to customers and solution to customer’s problem. The study recommended that pharmaceutical companies should try to be versatile in their collaborative strategy in a way so as to build a network with all their stakeholders in order to create value, boost their revenue profile towards the profitability posture of their organisation.